Aeration and Chemical Additives Prevent Hyperhydration and Allow the Production of High-Quality In Vitro Potato Plantlets - Pál Szarvas; Judit Dobránszki (Agronomy)
The production of healthy propagating material of the potato (Solanum tuberosum L.) is based on in vitro micropropagation. In vitro conditions, however, can cause stress leading to reduced quality, growth and development of in vitro plantlets. The effects of aeration and chemical additives on the in vitro growth and development and quality of potato plantlets were investigated. Four different jar closure types were tested, i.e., an intact metal cap (control), two layers of semi-permeable plastic foil, a metal cap with a single hole, or a metal cap with three holes. Under tightly sealed conditions (intact metal cap) the effects of silver nitrate (2.0 mg L−1) and 1-naphtylacetic acid (0.1 mg L−1) alone or in combination with each other, meta-topoline (0.1 mg L−1), ascorbic acid (10.0 mg L−1), salicylic acid (0.1 mg L−1), jasmonic acid (0.1 mg L−1) and glutamic acid (0.3 mg L−1) were studied. Morpho-physiological parameters were measured at the end of the subculture. Leaf development was a good indicator of the presumed ethylene effect. The development and quality of the plantlets were best in cultures sealed with three-holed caps. Of the chemicals applied, only the presence of silver nitrate resulted in high-quality plantlets. The combined application of silver nitrate and 1-naphthaleneacetic acid promoted root growth and development.